Pengaruh Persepsi Keamanan, Kemudahan Bertransaksi, Harga, Dan Kualitas Informasi Terhadap Minat Beli Ulang Melalui Kepuasan Pelanggan Pada Online Travel Agency (OTA) Traveloka.com - Munawaroh Munawaroh; Hary Sulaksono; Tamriatin Hidayah (Program Studi Manajemen, Sekolah Tinggi Ilmu Ekonomi Mandala, 2022)
This study aims to analyze the effect of perceived security, ease of transaction, price and quality of information on buying interest through customer satisfaction at the Online Travel Agency (OTA) Traveloka.Com. This research method uses descriptive quantitative research, data collection techniques use purposive sampling by distributing 60 questionnaires to STIE Mandala Jember students, the analytical method used is path analysis using SPSS version 20 and Sobel test calculator to test hypotheses. The results of this study indicate that: 1) the perceived security, price and quality of information variables have a direct effect on customer satisfaction at the Online Travel Agency (OTA) Traveloka.Com, while the ease of transacting variable has no direct influence, 2) the ease of transaction and quality of information variables. Information has a direct effect on buying interest at the Online Travel Agency (OTA) Traveloka.Com, while the perceived security and price variables do not have a direct influence, 3) customer satisfaction has a direct influence on buying interest at the Online Travel Agency (OTA) Traveloka. Com, and finally 4) the customer satisfaction variable cannot mediate the relationship between the variables of perceived security, ease of transaction, price and quality of information on buying interest through customer satisfaction at the Online Travel Agency (OTA) Traveloka.Com.